Fluka Monte Carlo for Validating Low-Energy Neutron Capture Therapy Tissue with Boron and Gadolinium - Bakolia, T. E.; Didi, A.; Sebihi, R.; Adambounou, K.; Hazou, E. (National Research and Innovation Agency, 2024)
Research Gap: Neutron Capture Therapy (NCT) represents a cutting-edge neutron-therapy technique for tumor treatment, but there is a gap in understanding the optimization of neutron dose deposition in tumor cells, particularly in tissues enriched with boron and gadolinium. Research Objective: This study aims to evaluate the dose deposited by thermal neutrons in adipose tissues enriched with boron and gadolinium, utilizing the Monte Carlo Fluka code. Research Methodology: The research employs Fluka, an open source Monte Carlo simulations to assess thermal neutron dose deposition in tissues. The focus is on boron and gadolinium-enriched tissues to understand their impact on neutron dose optimization. Results: Findings affirm the advantages of boron and gadolinium in enhancing neutron dose deposition within tissues. Fluka simulations demonstrate the strategic utilization of neutron properties, showcasing the potential for improved tumor management. The study highlights gadolinium's attractiveness, suggesting its promising application in clinical settings.